Borrowed Nouns - Adalar, Nevin; Tagliamonte, Sali A. (My University, 1998)
In this paper we provide a quantitative analysis of the behavior of nouns in two generations of speakers from a bilingual community in northern Cyprus. Diagnostics from three areas of grammar-phonology, morphology, and syntax-provide corroborating evidence that when a lone noun, of either English or Turkish origin, appears in contexts in which it is surrounded by the other language, it patterns systematically in accordance with its counterparts in that other language. On the other hand, when a lone noun, either English or Turkish, appears within a multiword fragment of English or Turkish, it patterns overwhelmingly with the language of its etymology. The strikingly different grammatical patterns highlight the fact that they represent two different types of behavior: borrowing in the former; codeswitching in the latter. These findings demonstrate that empirical investigation can disambiguate the community-specific status of language contact phenomena. Further, contrastive analysis across generations reveals that although the generations differ in the frequency with which they use Turkish and English, they employ the same strategies when they do. These strategies have far more to do with their preferred language of discourse, than with any purely linguistic factor.
Bilingual People: The case of the "Londrali" in Northern Cyprus
Keywords: Codeswitching; Integration; Loanword; Nonce borrowing; Turkish-English